Reindeer (Rangifer tarandus tarandus) perception of noise from power lines - Flydal, Kjetil; Kilde, Ingrid Rogstad; Enger, Per S.; Reimers, Eigil (Rangifer, 2003)
There has been concern about possible effects of noise from power lines on reindeer (Rangifer tarandus tarandus) behaviour. Based on recent establishment of the reindeer audiogram and measurements of corona noise from two power lines of 300 kV and 420 kV, we found that reindeer are able to hear noise from power lines at frequencies above 250 Hz. A comparison with the human audiogram shows that humans are better able to perceive noise from power lines than reindeer, at least at the lowest frequencies. By simple comparisons of this kind, the perception of different types of sound by reindeer can be determined. Possible noise disturbances from human activities and constructions can be minimised if the intensity can be reduced for frequencies in the best hearing range of reindeer.